ANALISIS BAURAN PROMOSI PENGGUNAAN sMartCU PADA USAHA ANGGOTA CREDIT UNION SAUAN SIBARRUNG DI TORAJA - Enggane Limbongan, Mey; Suba Sampewai, Melvis Putri Prasintia (JSSHA ADPERTISI JOURNAL, 2023)
The aim of this research is to analyze the promotional mix for the use of sMartCU in the member businesses of the Sauan Sibarrung Credit Union in Toraja. The type of research used in this research is a descriptive qualitative method with survey techniques. The descriptive qualitative method is research that attempts to provide proof of the truth of facts that occur in the field, situations based on a theoretical framework and the problems raised. The data collection techniques used were interviews and observations. The data processing technique used begins with data reduction, data presentation and drawing conclusions. From the research results, it was found that the use of sMartCU is very influential in introducing products to the people who are marketing targets, and providing value exchange based on the benefits provided by the product. The marketing tools used are advertising, sales promotions, events and experiences, public relations and publicity, and online marketing.